Hazardous waste minimization (McGraw-Hill, 1990)
The book presents a wealth of practical suggestions and directions for getting waste minimization programs off the ground: specific guidance in implementing industrial waste minimization programs, practical tools to sell the adea of waste minimization, summaries of waste reduction technologies, case studies of how to encourage communities and individuals to get involved in reducing wastes, details of assessment